2020
DOI: 10.1002/ajoc.202000582
|View full text |Cite
|
Sign up to set email alerts
|

Selenium‐NMR Spectroscopy in Organic Synthesis: From Structural Characterization Toward New Investigations

Abstract: This review article deals with organic synthesis from the perspective of selenium-77 nuclear magnetic resonance (NMR) spectroscopy. Different types of organic reactions are briefly discussed, incorporating mechanism aspects through 77 Se NMR observable intermediates and byproducts. The 77 Se NMR experiments are demonstrated in terms of structural characterization and new insights for organic reactions. The ability to visualize different molecules in a reaction mixture provides a facile and versatile route for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 169 publications
(420 reference statements)
1
25
0
Order By: Relevance
“…We proposed that the reaction of 12 and Cys would generate intermediate 12a and products including H 2 Se, 10 , and 13 (Figure e), which were characterized by 77 Se­{ 1 H} NMR and HPLC. As expected, 12 (90 mM) in DMSO- d 6 exhibited a 77 Se peak (δ = 576 ppm) for selenoamide . During the reaction with Cys, a new 77 Se peak (δ = 250 ppm) was observed (Figure f), which may be assigned to the generation of intermediate selenol 12a .…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…We proposed that the reaction of 12 and Cys would generate intermediate 12a and products including H 2 Se, 10 , and 13 (Figure e), which were characterized by 77 Se­{ 1 H} NMR and HPLC. As expected, 12 (90 mM) in DMSO- d 6 exhibited a 77 Se peak (δ = 576 ppm) for selenoamide . During the reaction with Cys, a new 77 Se peak (δ = 250 ppm) was observed (Figure f), which may be assigned to the generation of intermediate selenol 12a .…”
Section: Resultssupporting
confidence: 71%
“…From the therapeutic viewpoint and for in vivo applications in H 2 Se-related biological research, ideal H 2 Se donors should be water-soluble and biocompatible compounds that can release H 2 Se slowly under controllable, tunable activation with a clear triggering mechanism . To this end, we shifted to investigate arylselenoamides (Scheme ) because the analogue arylthioamides are water-soluble and reported to be very slowly activated by Cys. , Synthesis of selenobenzamide 5 was facilely achieved by the reaction of WR and benzamide in toluene at 130 °C in a sealed tube for 30 min . To prepare the selenobenzamide derivatives, we treated 4-hydroxybenzonitrile with selenium powder and sodium borohydride to produce 6 , which was further coupled with acetic acid to give 7 .…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the LC/MS data showed that the products were seleninic acid 18 and a dehydroalanine (Dha) derivative 20, respectively (Scheme 6). On the basis of 77 Se NMR spectroscopy data [54] (Figure 3A), alkyl seleninic acid 18 (RSeO 2 H 1217.5 ppm, [M + Na] = 471.0633) was formed after 1 h of irradiation. Our attempts to isolate oxidized form of 1 a failed due to product lability.…”
Section: Resultsmentioning
confidence: 99%
“…77 Se is a spin-1 2 NMR isotope with broad chemical shift range (ca. 3000 ppm), which makes it promising as a selective probe [25,[27][28][29]. Direct 77 Se NMR detection [30,31] is, however, unfavorable owing to the low natural abundance (7.63%) and decreased sensitivity (0.7 of 1 H) of this nucleus.…”
Section: Introductionmentioning
confidence: 99%